If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 6x + x = 22 Combine like terms: 6x + x = 7x -6 + 7x = 22 Solving -6 + 7x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 7x = 22 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 22 + 6 7x = 22 + 6 Combine like terms: 22 + 6 = 28 7x = 28 Divide each side by '7'. x = 4 Simplifying x = 4
| p/8=6 | | g/5=7 | | 10+4x-7x=-8 | | 8x+60=10x+50 | | 2*2+3y=5 | | .4n+5.2=12 | | 3x+21/4+x+44/7=16 | | 2x=242 | | F-8=-6 | | -57=3x+6x+6 | | 8+17r-6=9r+106-5r | | -5(-2)(3)(-1)(-7)=210 | | 4(4x-9)=28 | | -6(-2)(3)(-4)(1)=144 | | 2x^2=-242 | | 2h+10=62 | | 2h+10=62 | | 2x^2=-242 | | -4/3s=-16 | | 3(2k-0.5)=17.85 | | -63/-9=7 | | 1x+12=70 | | -30v-8=12 | | 9z-z=-3 | | 2(5x+3)=76 | | x+0.8,9.2=x+0.2 | | (-14)(20)=-280 | | 6x=3x+1 | | 8z-z=-1+2z-3 | | 3x/5-2(x/10-4)=2x+6 | | 5.3a+10=63 | | (w^9)^1/3 |